Enhanced photocatalytic degradation of methylene blue dye under UV-sunlight irradiation by cesium doped chromium oxide thin films. (November 2017) - Larbi, T.; Amara, M.A.; Ouni, B.; Amlouk, M.
Graphical abstract: Highlights: Cs doped thin films has been prepared by the low- cost spray pyrolysis technique. Enhanced photocatalytic activity of Cr2O3 thin films for MB photogegradation(MB) dye was achieved through Cs doping. 6 % Cs doped Cr2 O3 thin film photocatalyst with the merits of low band gap and more oxygen vacancies, exhibits the highest sun-light photocatalytic activity. High photostability and recyclability was achieved under sun-light irradiation. Abstract: The present contribution highlights the photocatalytic degradation of methylene blue dye over chromium oxide Cr2 O3 thin films based photocatalysts illuminated by ultraviolet and sunlight. Cr2 O3 photocatalyst was synthesized as thin film by the spray pyrolysis method on glass substrate at temperature of 350 °C. The physical properties of the thin films were studied by X-ray diffraction, scanning electron microscopy (SEM), infrared spectroscopy (IR), Raman spectroscopy, photoluminescence (PL) probing and UV–vis spectroscopy. XRD results showed that all samples were well crystallized with rhomoboedric curudum structure. Emissions of all films have been observed in visible region at 325 nm excitation. UV–vis-NIR spectrophotometry analysis showed that the band gap energy value of chromium oxide is shortened with cesium doping. Results indicate that both the cesium doping and the introduction of oxygen vacancies promote good photocatalytic activity of Cs doped Cr2 O3 thin films under sunlight for MB degradation.